1998
DOI: 10.1093/ndt/13.9.2341
|View full text |Cite
|
Sign up to set email alerts
|

Icodextrin use in CCPD patients during peritonitis: ultrafiltration and serum disaccharide concentrations

Abstract: In contrast to glucose, icodextrin preserved the daytime dwell ultrafiltration during peritonitis. Serum icodextrin metabolites increased during icodextrin use, but remained stable during peritonitis. Adverse effects were not observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 1 publication
0
27
0
Order By: Relevance
“…It is becoming increasingly clear that one of the primary responsibilities of clinicians in the management of PD patients is the balance between adequate control of fluid status and preservation of residual renal function. Numerous clinical studies (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(35)(36)(37) and more than 9 years of post-marketing surveillance have confirmed that icodextrin is a safe and well-tolerated osmotic alternative PD solution to glucose. The most significant adverse effect reported to date is a cutaneous hypersensitivity reaction (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…It is becoming increasingly clear that one of the primary responsibilities of clinicians in the management of PD patients is the balance between adequate control of fluid status and preservation of residual renal function. Numerous clinical studies (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(35)(36)(37) and more than 9 years of post-marketing surveillance have confirmed that icodextrin is a safe and well-tolerated osmotic alternative PD solution to glucose. The most significant adverse effect reported to date is a cutaneous hypersensitivity reaction (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…However, the beneficial effect of icodextrin on the glycemic control has not been confirmed in all studies [19]. Icodextrin preserves or even increases UF capacity during peritonitis, in contrast to glucose [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…In addition a reduced size selectivity is present in the early phase [5], leading to a decrease in the peritoneal restriction coefficient to macromolecules [24]. The presence of an increased effective peritoneal surface area leads to lower ultrafiltration rates on glucose-based solutions [22] and higher ultrafiltration rates on an icodextrin-based fluid [25,26]. These functional alterations are temporary and disappear after cure from the infection [22].…”
Section: Peritoneal Transport and Inflammatory Mediators During Peritmentioning
confidence: 99%